A study of early career teachers' practices related to language and language diversity during mathematics instruction. Issue 1 (2nd January 2019) - Turner, Erin; Roth McDuffie, Amy; Sugimoto, Amanda; Aguirre, Julia; Bartell, Tonya Gau; Drake, Corey; Foote, Mary; Stoehr, Kathleen; Witters, Angela
ABSTRACT: The role of language in mathematics teaching and learning is increasingly highlighted by standards and reform movements in the US. However, little is known about teachers', and especially early career teachers' (ECTs) practices and understandings related to language in mathematics instruction. This multiple case study explored the language-related understandings and practices of six ECTs in diverse elementary classrooms. Using iterative cycles of analysis, we found that all ECTs regularly attended to students' mathematical vocabulary use and development. Yet, there was variability in ECTs' focus on how to teach mathematical vocabulary, expectations for students' precise use of mathematical terminology, and the use of multiple languages during instruction. These findings indicate that ECTs need more targeted support during teacher preparation and early career teaching in order to better support all students' language development in the mathematics classroom.